2013
DOI: 10.1128/jb.00672-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fructose 1,6-Bisphosphatase and Sedoheptulose 1,7-Bisphosphatase from the Facultative Ribulose Monophosphate Cycle Methylotroph Bacillus methanolicus

Abstract: The genome of the facultative ribulose monophosphate (RuMP) cycle methylotroph Bacillus methanolicus encodes two bisphosphatases (GlpX), one on the chromosome (GlpX C ) and one on plasmid pBM19 (GlpX P ), which is required for methylotrophy. Both enzymes were purified from recombinant Escherichia coli and were shown to be active as fructose 1,6-bisphosphatases (FBPases). The FBPase-negative Corynebacterium glutamicum ⌬fbp mutant could be phenotypically complemented with glpX C and glpX P from B. methanolicus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 65 publications
2
44
0
1
Order By: Relevance
“…However, the plasmid-encoded enzyme also displayed activity toward sedoheptulose 1,7-bisphosphate whereas the chromosomal enzyme did not. This implies that the plasmid encoded fructose 1,6 bisphosphatase is the main enzyme of the RuMP regeneration pathway [25]. Similarly, the chromosomal fructose 1,6-bisphosphate aldolase exhibited higher catalytic efficiency for the aldol cleavage of fructose 1,6-bisphosphate, whereas the plasmid encoded version exhibited higher catalytic efficiency toward triose phosphates [26].…”
Section: Hcho Assimilation Via the Rump Pathwaymentioning
confidence: 97%
See 1 more Smart Citation
“…However, the plasmid-encoded enzyme also displayed activity toward sedoheptulose 1,7-bisphosphate whereas the chromosomal enzyme did not. This implies that the plasmid encoded fructose 1,6 bisphosphatase is the main enzyme of the RuMP regeneration pathway [25]. Similarly, the chromosomal fructose 1,6-bisphosphate aldolase exhibited higher catalytic efficiency for the aldol cleavage of fructose 1,6-bisphosphate, whereas the plasmid encoded version exhibited higher catalytic efficiency toward triose phosphates [26].…”
Section: Hcho Assimilation Via the Rump Pathwaymentioning
confidence: 97%
“…Second, several studies have compared the activities of both the plasmid and chromosomal RuMP-pathway regeneration genes and found that they possess somewhat different activities [24][25][26]. For example, the chromosomally encoded fructose 1,6 bisphosphatase had higher activity and a lower K m for fructose 1,6-bisphosphate compared with the plasmid-encoded copy.…”
Section: Hcho Assimilation Via the Rump Pathwaymentioning
confidence: 97%
“…The detection of high levels of hexulose‐6‐phosphate synthase (Hps) and 6‐phospho‐3‐hexuloisomerase (Phi) activity in cell‐free extracts of B. methanolicus made it likely that the RuMP pathway is employed for carbon assimilation (Dijkhuizen et al ., ; Arfman et al ., ). Genomic information together with transcriptome data, proteome data and enzymatic studies suggested that the fructose‐bisphosphate aldolase/sedoheptulose bisphosphatase variant of the RuMP cycle is used (Heggeset et al ., ; Stolzenberger et al ., 2013a,b; Müller et al ., ) (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…For growth on methanol, transcriptome and proteome data have demonstrated that only the plasmid‐encoded versions of the genes are upregulated (Heggeset et al ., ; Müller et al ., ). The reason for the gene duplication is not known, but characterization of some of the enzymes indicated that the chromosomal‐ and plasmid‐encoded enzymes differ in their biochemical properties (Stolzenberger et al ., 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes: MDH ,  methanol dehydrogenase (EC 1.1.1.244); HPS ,  3-hexulose-6-phosphate synthase (EC 4.1.2.43); PHI ,  6-phospho-3-hexuloisomerase (EC 5.3.1.27); PFK ,  6-phosphofructokinase, (EC 2.7.1.11); FBA ,  fructose-bisphosphate aldolase (EC 4.1.2.13); TKT ,  transketolase (EC 2.2.1.1); GlpX ,  fructose-bisphosphatase (EC 3.1.3.1); TA ,  transaldolase (EC 2.2.1.2); RPE , ribulose- phosphate 3-epimerase (EC 5.1.3.1); RPI ,  ribose-5-phosphate isomerase (EC 5.3.1.6); Metabolites: H6-P, 3-hexulose 6-phosphate; F6-P, fructose-6-phosphate; FBP, fructose-1,6-bisphosphate; GAP, glyceraldehyde 3-phosphate; DHAP, dihydroxyacetone phosphate; E4-P, erythrose 4-phosphate; SBP, sedoheptulose 1,7-bisphosphate; S7-P, sedoheptulose-7-phosphate; Ri5-P, ribose 5-phosphate; X5P, xylulose 5-phosphate; Ru5P, ribulose 5-phosphate; The reactions are described in detail in the text. Adapted from [28]. …”
Section: Introductionmentioning
confidence: 99%